2021
DOI: 10.3389/fmolb.2020.558982
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics in Sickle Cell Disease Research: State of the Art and a Perspective Beyond the Flow Problem

Abstract: Sickle cell disease (SCD) is the monogenic hemoglobinopathy where mutated sickle hemoglobin molecules polymerize to form long fibers under deoxygenated state and deform red blood cells (RBCs) into predominantly sickle form. Sickled RBCs stick to the vascular bed and obstruct blood flow in extreme conditions, leading to acute painful vaso-occlusion crises (VOCs) – the leading cause of mortality in SCD. Being a blood disorder of deformed RBCs, SCD manifests a wide-range of organ-specific clinical complications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…23,73 As sickle cell anemia had relative low level of hematocrit ( i.e. , 20%–25%), 74–77 the present method could be regarded as one of the promising potentials for detecting sickle cell anemia.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…23,73 As sickle cell anemia had relative low level of hematocrit ( i.e. , 20%–25%), 74–77 the present method could be regarded as one of the promising potentials for detecting sickle cell anemia.…”
Section: Resultsmentioning
confidence: 92%
“…In the near future, if the issues raised by the proposed method are fully resolved (i.e., smartphone or portable pump), the proposed method can be considered as a promising method for monitoring blood samples circulating under an in vitro or ex vivo circuit. 23,73 As sickle cell anemia had relative low level of hematocrit (i.e., 20%-25%), [74][75][76][77] the present method could be regarded as one of the promising potentials for detecting sickle cell anemia.…”
Section: Detection Of Aggregation-elevated Blood With Averaged Work A...mentioning
confidence: 96%
“…RBCs’ biophysical phenotyping is of great practical importance [ 51 , 52 ]. It has already been shown that microfluidic analysis can successfully register RBCs disorders [ 21 , 31 , 41 , 53 ]. For improving the analysis of the functional characteristics of RBCs, the microfluidic device must provide high sensitivity to deviations from the physiological norm and establish a standard experimental procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a microfluidic assay to measure RBCs occlusions under various conditions in vitro was developed to evaluate the clinical efficiency of different drug therapy [ 30 ]. Moreover, microfluidic analysis has been successfully used for the biophysical characterization of sickle cell erythrocytes, allowing in vitro modeling of an oxygen gradient, a trigger factor for developing occlusive crises during polymerization of hemoglobin S in these patients [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, ISCs obstruct microvessels, altering the normal circulation of blood. In the last decade, microfluidic devices have played the important role of determining the biophysical characteristics of sickle red cells [175], measuring the mechanical stresses on erythrocytes in sickle cell disease [176], studying vaso-oclusion [104,177,178], identifying biophysical markers [179,180], segregating sickle cells [181], and developing point-of-care diagnostic technologies for low-resource settings [182] and possible treatments [183].…”
Section: Hemorheological Pathologies and Emergent Microfluidics Diagn...mentioning
confidence: 99%